Association of gestational diabetes mellitus and negative modulation of the specific humoral and cellular immune response against Toxoplasma gondii - Oliveira-Scussel, Ana Carolina de Morais; Ferreira, Paula Tatiana Mutão; Resende, Renata de Souza; Ratkevicius-Andrade, Cristhianne Molinero; Gomes, Angelica de Oliveira; Paschoini, Marina Carvalho; De Vito, Fernanda Bernadelli; Farnesi-de-Assunção, Thaís Soares; Silva, Marcos Vinícius da; Mineo, José Roberto; Rodrigues, Denise Bertulucci Rocha; Rodrigues, Virmondes (Frontiers in Immunology, 2022)
In order to evaluate and compare the specific immune response of pregnant women (PW) chronically infected with Toxoplasma gondii, with and without gestational diabetes mellitus (GDM), and the humoral response of their respective newborns (NB), the study was carried out on 81 PW (34 GDM and 47 controls) from whose medical records the results of the oral glucose tolerance test (OGTT) were obtained, and blood samples were collected at the third trimester of pregnancy; also, on 45 NBs (20 GDM and 25 controls) from whom umbilical cord blood samples were obtained. Humoral immunity was analyzed by measuring anti-T. gondii total IgG, IgG subclasses and IgG avidity. To evaluate cellular immunity, peripheral blood mononuclear cells (PBMC) from 32 PW (16 GDM and 16 controls) were cultured, supernatant cytokines were determined, and flow cytometry was performed to analyze the expression at lymphocytes of surface molecules, cytokines and transcription factors. All PW and NBs were positive for total IgG, and the prevalent subclass was IgG1. There was a negative correlation between the OGTT glycemia of PW and the levels of total IgG, IgG1 and IgG avidity. The IgG avidity of the GDM group was significantly lower than the control group. Patients from the GDM group had a higher number of T lymphocytes expressing markers of cell activation and exhaustion (CD28 and PD-1). In the presence of T. gondii soluble antigen (STAg) the amount of CD4+ T cells producing IFN-γ, IL-10 and IL-17 was significantly lower in the GDM group, while there was no difference between groups in the number of CD4+ CD25HighFOXP3+LAP+ functional Treg cells. Additionally, under STAg stimulus, the secretion of IL-17, IL-4, TNF and IL-2 cytokines at PBMCs culture supernatant was lower in the GDM group. In conclusion, there was a correlation between the increase in blood glucose and the decrease in levels of anti-T. gondii antibodies, associated with the decreased IgG avidity in patients who develop GDM. Also, the GDM group had decreased immune responses in Th1, Th2 and Th17 profiles, suggesting an association between GDM and the negative modulation of the humoral and cellular immune responses against T. gondii.